Investigating Indonesian Pre-Service Teachers’ Beliefs about English Language Learning - Alifya Ramadhani; Daflizar (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study sought to investigate the language learning beliefs of Indonesian pre-service teachers and determine whether these beliefs varied according to gender and majors of study. Employing a quantitative approach with a survey design, the study involved 69 pre-service teachers from English and non-English majors at an Islamic higher education institution in Jambi Province, Indonesia. The data were collected using an online questionnaire administered during classroom sessions and analyzed using SPSS through descriptive and inferential statistics. The findings revealed that the participants held diverse, multidimensional, and generally positive beliefs about language learning, covering aspects such as language aptitude, learning difficulty, the nature of language learning, motivation, and learning strategies. Statistical analysis further showed that there were statistically significant differences in beliefs between male and female pre-service teachers (p < .05) but no significant differences were found regarding majors of study (p > 0.05). The study provides implications for educational institutions, teacher educators, and learners in supporting positive language learning beliefs within the Indonesian EFL context.